Understanding Human Resource Management: Exploring Psychological Dynamics and Strategic Approaches through Qualitative Description and Literature Review - Syam, Shofiana (Manunggal Halim Jaya, 2024)
This qualitative research study aims to explore the intersection of human resource management (HRM) practices with psychological dynamics and strategic approaches. The research methodology involves a systematic literature review to analyze existing literature on HRM, psychological theories, and strategic HRM practices. Through comprehensive literature search and selection, relevant sources were identified from academic databases, scholarly journals, and books. Data extraction and analysis were conducted using thematic analysis techniques to identify key themes, concepts, and findings related to psychological dynamics and strategic HRM. The findings reveal the critical role of psychological theories, such as Maslow's Hierarchy of Needs and Herzberg's Two-Factor Theory, in understanding employee motivations and behaviors. Additionally, strategic HRM approaches, including Guest's model and High-Performance Work Systems (HPWS), were identified as effective frameworks for aligning HRM practices with organizational goals. The integration of technology, such as artificial intelligence and predictive analytics, emerged as a key trend in enhancing HRM efficiency and effectiveness. Overall, this research highlights the importance of addressing employees' psychological needs and leveraging strategic HRM practices to foster organizational success and employee well-being.